EFICIÊNCIA DO USO DO NITROGÊNIO E DESEMPENHO AGRONÔMICO DO MILHO EM SISTEMA DE PLANTIO DIRETO NA PALHA DE LEUCENA NO TRÓPICO ÚMIDO - SILVA, Anagila Janenis Cardoso (2016)
In the humid tropical soils, the efficiency of nutrient use is very low, especially those required in larger quantities by plants, such as nitrogen. The objectives of this study were to evaluate the effect of using leucena legume biomass coverage associated with mineral fertilizer and humic acid on the availability and efficiency of use of N; evaluate the agronomic performance of the variety of corn QPM BR 473 associated with the following treatments: 133 kg ha-1 of urea as a source of nitrogen (N); 15 t ha-1 leucena (L); 133 kg ha-1 of urea + 15 t ha-1 leucena (N + L); 500 L ha-1 humic acid + 15 t ha-1 leucena (AH + L); 500 L ha-1 humic acid + 133 kg ha-1 of urea (AH + N) and 500 L ha-1 humic acid + 133 kg ha-1 of urea + 15 t ha-1 leucena (AH + N + U). All treatments received 120 kg ha-1 of P2O5, 60 kg ha-1 of K2O and 25 kg ha-1 ZnSO4. The N + L treatment was the highest productivity (5385 kg ha-1), nitrogen remobilization (35.20 kg ha-1), agronomic efficiency (32.61 kg kg-1) and higher recovery efficiency (52.44%). For this investigation, with the data efficiencies mainly shows the agronomic and nitrogen recovery efficiency and nitrogen remobilized and grain production, it can be inferred that the combination of biomass leucena with urea showed the highest productivity , noting that the use of these two sources of nitrogen together in tillage system is an important alternative for small producers in the humid tropics. Therefore, the effect of the existing synchronization between the release of nitrogen by organic and mineral sources was well demonstrated by the data presented in this study, however, the synergy of these sources with the humic acid was not fully clarified. Thus, increasing the efficiency of nutrients by plants through novel mechanisms as the application of humic acid may be a means of improving productivity. However, it is still necessary to better understand the mechanisms involved in this process to improve them.